Development of a Technology Roadmap for the Philippine Courier, Express & Parcel Industry Technology The Case of BRIDGE POINT CARGO-LOGISTICS EXPERT INC. - Carlos, Jonathan Cruz (University of the Philippines Diliman, 2012)
The logistics and courier industry is one of the oldest business sectors in the world with its origins and history dating back when the Persians where invading Greece. Couriers and the concept of logistics though not yet formally invented, was also used during the time of kings and queens in medieval times. Throughout the course of history, the role of logistics and couriers in the economy has evolved to where it is now. Nowadays where the global economy is exponentially growing, the role of logistics in an economy's growth is becoming more vital to sustain its growth. Global value chains (GVC) are one of the main beneficiaries of the courier industry. Studies show that the industry employs a variety of manpower skillset ranging from engineering to managerial. From a macro-economic perspective, its impact in GVCs and the supply chain is determined by factors like speed of delivery, reliability, and customer service. The Worldbank's Logistics Performance Index (LPI) is just one of the determinants of a country's "logistics friendliness". By conducting surveys and assessing a country based from a list of criteria, certain areas of improvement may be deduced. This paper aims to produce a firm-level technology roadmap of the Philippine courier and logistics sector. Bridge Point Cargo Logistics Expert Inc. will serve as the organization to evaluate in terms of internal and external factors. At the end of the roadmapping activity, the output and its implementation will be criticized. Further recommendations and courses of action shall also be suggested in order to improve the technology roadmap report.